Identifying needs and expectations of potential users of the virtual platform to foster healthy and active ageing in Andalusia. Issue 1 (2018) - Samaniego, López; Matillas, Bibiana Navarro; Almendro, Juan Manuel Espinosa; Lozano, Pilar San Juan
No abstract available